Wear-resistant self-lubricating hydrogen-free carbon-based coating on surface of oilless bearing and preparation method thereof
By using C targets to deposit a hydrogen-free carbon-based coating, the safety and service life problems caused by the use of flammable gases in the prior art are solved, and high-performance wear-resistant self-lubricating effect is achieved, and protection is provided under high temperature conditions is provided. .
Patent Information
- Application Number
- CN202411621958.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing wear-resistant self-lubricating coatings in oil-free bearings have reduced process safety due to the use of flammable and explosive gases such as methane or acetylene, and may cause hydrogen embrittlement and cracking, affecting the service life of the coating.
Using C target as carbon source, hydrogen-free carbon-based coatings are deposited through magnetron sputtering technology, including binding force layers, wear-resistant self-lubricating coatings and surface C layers, avoiding the use of flammable gases and passing oxygen plasma The treatment improves the bond strength between the surface C layer and the wear-resistant self-lubricating coating.
It improves the service life of the coating, enhances the self-lubricating performance, reduces the friction between the various components of the oil-free bearing, ensures process safety, and achieves high-performance protection under high temperature conditions.
Smart Images

Figure CN119506773A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wear-resistant self-lubricating coatings, and in particular to a wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing and a preparation method thereof. Background Art
[0002] Oil-free bearings are widely used in various mechanical rotating devices, especially in some vacuum devices that require oil-free lubrication. Due to factors such as load and friction, the surface of oil-free bearings will be severely worn and fail. Therefore, the surface coating of oil-free bearings is required to have wear-resistant and self-lubricating properties.
[0003] Existing wear-resistant self-lubricating coatings generally use methane, acetylene and other gases as reaction gases to deposit carbon elements. Since methane and acetylene are both flammable and explosive gases, the safety of the process is reduced. In addition, the hydrogen elements in methane and acetylene will cause subsequent hydrogen embrittlement and cracking of the coating, affecting the service life of the coating.
[0004] Based on the above technical problems, the present application proposes a wear-resistant, self-lubricating, hydrogen-free carbon-based coating on the surface of an oil-free bearing and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing and a preparation method thereof, so as to solve the technical problems mentioned in the background technology. The purpose of the present invention is achieved through the following technical solutions:
[0006] A wear-resistant, self-lubricating, hydrogen-free carbon-based coating on the surface of an oil-free bearing comprises a bonding layer, a wear-resistant, self-lubricating coating and a surface C layer, wherein the bonding layer, the wear-resistant, self-lubricating coating and the surface C layer are sequentially arranged on the surface of the oil-free bearing from bottom to top by magnetron sputtering; the wear-resistant, self-lubricating coating is a carbon-based metal compound coating or a carbon-containing nano-multilayer coating, and the carbon element in the wear-resistant, self-lubricating coating accounts for 54.3%-72.3% by mass.
[0007] Furthermore, the bonding layer is a Cr metal layer or a Ti metal layer.
[0008] Furthermore, the surface C layer is a graphite layer or a ta-C layer.
[0009] The present application also discloses a method for preparing a wear-resistant, self-lubricating, hydrogen-free carbon-based coating on the surface of any of the above-mentioned oil-free bearings, comprising the following steps:
[0010] Step S1, glow cleaning;
[0011] Step S2, high energy ion cleaning;
[0012] Step S3, preparing a bonding layer;
[0013] Step S4, preparing a wear-resistant self-lubricating coating;
[0014] Step S5, preparing a surface C layer.
[0015] Further, the glow cleaning process is as follows:
[0016] Set the argon flow rate to 80-150 sccm, the working gas pressure to 0.8-3.0 Pa, the bias power supply to -500-800 V, and the glow clearing time to 60-120 min.
[0017] Further, the high energy ion cleaning process is as follows:
[0018] The argon gas flow rate is set to 80-100 sccm, the working gas pressure is set to 0.8-1.0 Pa, the high-power pulsed magnetron sputtering power supply target voltage pulse width is set to 1-4 μs, the average power is set to 5-8 kW and the negative bias power supply is set to -300-500 V, the sputtering target is Cr or Ti metal target, and the high-energy ion cleaning time is set to 5-10 minutes.
[0019] Furthermore, the bonding layer preparation process is as follows:
[0020] The argon flow rate is set to 80-100 sccm, the working gas pressure is set to 0.8-1.0 Pa, the high-power pulsed magnetron sputtering power supply target voltage pulse width is set to 1-4 μs, the average power is set to 5-8 kW and the negative bias power supply is set to -30--100 V, the sputtering target is Cr or Ti metal target, and the deposition time is set to 10-20 min.
[0021] Furthermore, the preparation process of the wear-resistant self-lubricating coating is as follows:
[0022] Set the argon flow rate to 80-100 sccm, the nitrogen flow rate to 20-60 sccm, the working gas pressure to 0.8-1.0 Pa, set the high-power pulsed magnetron sputtering power supply target voltage pulse width to 1-4 μs, the average power to 5-8 kW and the negative bias power supply to -30--100 V, the sputtering target materials are C target material and metal target material, or C target material and metal alloy target material, and the deposition time is 10-30 min.
[0023] Furthermore, the surface C layer preparation process is as follows:
[0024] Step S51, setting the oxygen flow rate to 80-150 sccm, the working gas pressure to 0.8-3.0 Pa, the bias power supply to -500-800 V, and the glow cleaning time to 5-10 min;
[0025] Step S52, set the argon gas flow rate to 50-180sccm, the working gas pressure to 0.2-3Pa, set the high-power pulsed magnetron sputtering power supply target voltage pulse width to 10-50μs, the average power to 6-12kW and the bias power supply to -300--800V, the sputtering target material to C target material, and the deposition time to 5-20min.
[0026] The technical solution provided in the embodiments of the present application has at least the following technical effects or advantages:
[0027] 1. The use of C target as the carbon source avoids the use of flammable and explosive gases such as methane and acetylene, ensures the safety of the process, reduces the risk of subsequent hydrogen embrittlement and cracking of the coating, and increases the service life of the coating;
[0028] 2. The self-lubricating performance of the coating is further improved by setting the surface C layer, the friction between the components of the oil-free bearing is reduced, and the service life of the oil-free bearing is extended; at the same time, oxygen plasma treatment is performed before depositing the surface C layer, which improves the bonding strength between the surface C layer and the wear-resistant self-lubricating coating and increases the service life of the coating;
[0029] 3. The preparation method of the present application has the advantages of fast deposition rate, simple operation, low cost, nano-hardness of the coating of 30-42GPa, H / E* (E* is the effective Young's modulus) ≥ 0.1, uniformity ≥ 96%, H 3 / E* 2 ≥0.3, membrane-base bonding strength (Rockwell indentation bonding strength ≥HF1, scratch bonding strength ≥30N), fracture toughness K IC ≥3MPa·m 1 / 2 , friction coefficient ≤ 0.1, can achieve high performance protection at high temperature above 800℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The drawings in the specification, which constitute a part of this application, are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0031] Figure 1 This is a schematic diagram of the structure of an embodiment of the present application;
[0032] Figure 2 The relationship between the coating hardness / elastic modulus and the C content in the embodiment of the present application;
[0033] Figure 3 This is a process flow chart of an embodiment of the present application;
[0034] Figure 4 This is a graph showing the results of HRC indentation bonding strength and scratch bonding strength testing in the embodiment of this application;
[0035] Figure 5This is a fracture toughness test result diagram of the embodiment of the present application;
[0036] Figure 6 This is a friction coefficient curve diagram of an embodiment of the present application.
[0037] Markings in the attached figure: 1. Adhesion layer; 2. Wear-resistant self-lubricating coating; 3. Surface C layer. DETAILED DESCRIPTION
[0038] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the drawings and specific implementation methods of the specification. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] like Figure 1 The wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing shown in the figure comprises a bonding layer 1, a wear-resistant self-lubricating coating 2 and a surface C layer 3, which are sequentially deposited on the surface of the oil-free bearing from bottom to top by magnetron sputtering. Specifically, the wear-resistant self-lubricating hydrogen-free carbon-based coating is deposited on the working surface of the oil-free bearing, i.e., the outer wall of the inner ring, the outer surface of the ball and the inner wall of the outer ring, and the oil-free bearing can be a metal bearing or a ceramic bearing.
[0041] The bonding layer 1 is a Cr metal layer or a Ti metal layer, and its function is to enhance the bonding strength between the wear-resistant self-lubricating coating 2 and the oil-free bearing.
[0042] The thickness of the wear-resistant self-lubricating coating 2 is 0.5-2μm. The wear-resistant self-lubricating coating 2 is a carbon-based metal compound coating such as CrCN, WC, TiCN, TiAlSiCN, TiVSiCN and TiSiCN. The wear-resistant self-lubricating coating 2 can also be a carbon-containing nano multilayer coating such as Cr / CrCN / C, Cr / WC / C, Ti / TiCN / C, etc.
[0043] The hardness / elastic modulus value is a common indicator for judging the wear resistance of coatings. Figure 2As shown, with the increase of C content, the wear resistance of the coating shows a trend of first increasing and then decreasing, and when the carbon content in the wear-resistant self-lubricating coating is 54.3%-72.3% by mass percentage, the wear-resistant self-lubricating coating 2 has better wear resistance, and when the carbon content is 65.3%, the wear resistance of the wear-resistant self-lubricating coating 2 is the best. Therefore, when preparing the wear-resistant self-lubricating coating 2, the content of carbon in the wear-resistant self-lubricating coating 2 is adjusted by selecting different proportions of target materials or different deposition processes to improve the wear resistance of the wear-resistant self-lubricating coating 2.
[0044] The thickness of the surface C layer 3 is 0.1-0.2 μm, and the surface C layer 3 is a graphite layer or a ta-C layer. The surface C layer 3 can significantly reduce the friction coefficient of the oil-free bearing surface. Preferably, the surface C layer 3 is a ta-C layer, and its sp 3 A higher content provides higher hardness and temperature resistance, and can significantly reduce the friction coefficient.
[0045] Example 2
[0046] Place the substrate in a container of anhydrous alcohol or acetone, clean it with an ultrasonic cleaning instrument for 30 to 60 minutes, take it out and blow dry it with compressed air, place it on the sample stage of a four-target closed-field unbalanced magnetron sputtering device, close the door and evacuate until the vacuum degree is lower than 1 × 10 -4 Pa.
[0047] like Figure 3 As shown, a method for preparing a wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing in Example 1 comprises the following steps:
[0048] Step S1, glow cleaning;
[0049] The glow cleaning process is as follows:
[0050] Set the argon flow rate to 80-150 sccm, the working gas pressure to 0.8-3.0 Pa, the bias power supply to -500-800 V, and the glow clearing time to 60-120 min.
[0051] Step S2, high energy ion cleaning;
[0052] The high energy ion cleaning process is as follows:
[0053] The argon gas flow rate is set to 80-100 sccm, the working gas pressure is set to 0.8-1.0 Pa, the high-power pulsed magnetron sputtering power supply target voltage pulse width is set to 1-4 μs, the average power is set to 5-8 kW and the negative bias power supply is set to -300-500 V, the sputtering target is Cr metal or Ti metal target, and the high-energy ion cleaning time is set to 5-10 minutes.
[0054] Step S3, preparing a bonding layer;
[0055] The preparation process of the bonding layer is as follows:
[0056] The argon gas flow rate is set to 80-100 sccm, the working gas pressure is set to 0.8-1.0 Pa, the high-power pulsed magnetron sputtering power supply target voltage pulse width is set to 1-4 μs, the average power is set to 5-8 kW and the negative bias power supply is set to -30--100 V, the sputtering target is Cr metal or Ti metal target, and the deposition time is set to 10-20 min.
[0057] Step S4, preparing a wear-resistant self-lubricating coating;
[0058] The preparation process of wear-resistant self-lubricating coating is as follows:
[0059] Set the argon flow rate to 80-100 sccm, the nitrogen flow rate to 20-60 sccm, the working gas pressure to 0.8-1.0 Pa, set the high-power pulsed magnetron sputtering power supply target voltage pulse width to 1-4 μs, the average power to 5-8 kW and the negative bias power supply to -30--100 V, the sputtering target materials are C target material and metal target material such as Cr, Ti, etc., or C target material and metal alloy target material such as WC, TiAlSi, TiAl, TiVSi, TiSi, Si, CrAl, etc., or combined target material such as Cr / C, Ti / C, etc., and the deposition time is 10-30 min.
[0060] Step S5, preparing a surface C layer;
[0061] The surface C layer preparation process is as follows:
[0062] Step S51, set the oxygen flow rate to 80-150sccm, the working gas pressure to 0.8-3.0Pa, the bias power supply to -500-800V, and the glow cleaning time to 5-10min; the surface of the wear-resistant self-lubricating coating 2 after oxygen plasma treatment is grafted with oxygen-containing functional groups, so that the surface activity of the wear-resistant self-lubricating coating 2 is enhanced, which is more conducive to the deposition of the surface C layer.
[0063] Step S52, set the argon gas flow rate to 50-180sccm, the working gas pressure to 0.2-3Pa, set the high-power pulsed magnetron sputtering power supply target voltage pulse width to 10-50μs, the average power to 6-12kW and the bias power supply to -300--800V, the sputtering target material to C target material, and the deposition time to 5-20min.
[0064] like Figure 4 As shown in the figure, after HRC indentation bonding strength and scratch bonding strength testing, the coating has no cracks and no shedding, the critical load of scratch bonding strength is greater than 30N, and there is no coating rupture and failure phenomenon, indicating that the bonding strength between the coating and the substrate is strong.
[0065] like Figure 5As shown, after the fracture toughness test, from left to right, there are 10g, 25g, and 50g micron indentations. The results show that no cracks are generated in the indentations, indicating that the coating has good toughness and crack resistance. The fracture toughness K IC ≥3MPa·m 1 / 2 .
[0066] like Figure 6 As shown, the friction coefficient of the coating is extremely low, about 0.08, indicating that the coating has good lubrication properties, uniform microstructure, and excellent wear resistance.
[0067] The technical solution provided in the embodiments of the present application has at least the following technical effects or advantages:
[0068] 1. The use of C target as the carbon source avoids the use of flammable and explosive gases such as methane and acetylene, ensures the safety of the process, reduces the risk of subsequent hydrogen embrittlement and cracking of the coating, and increases the service life of the coating;
[0069] 2. The self-lubricating performance of the coating is further improved by setting the surface C layer, the friction between the components of the oil-free bearing is reduced, and the service life of the oil-free bearing is extended; at the same time, oxygen plasma treatment is performed before depositing the surface C layer, which improves the bonding strength between the surface C layer and the wear-resistant self-lubricating coating and increases the service life of the coating;
[0070] 3. The preparation method of the present application has the advantages of fast deposition rate, simple operation, low cost, nano-hardness of the coating of 30-42GPa, H / E* (E* is the effective Young's modulus) ≥ 0.1, uniformity ≥ 96%, H 3 / E* 2 ≥0.3, membrane-base bonding strength (Rockwell indentation bonding strength ≥HF1, scratch bonding strength ≥30N), fracture toughness K IC ≥3MPa·m 1 / 2 , friction coefficient ≤ 0.1, can achieve high performance protection at high temperature above 800℃.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing, characterized in that: It includes a bonding layer, a wear-resistant self-lubricating coating and a surface C layer, wherein the bonding layer, the wear-resistant self-lubricating coating and the surface C layer are sequentially arranged on the surface of the oil-free bearing from bottom to top by magnetron sputtering; the wear-resistant self-lubricating coating is a carbon-based metal compound coating or a carbon-containing nano-multilayer coating, and the carbon element in the wear-resistant self-lubricating coating accounts for 54.3%-72.3% by mass.
2. The wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing according to claim 1, characterized in that: The bonding layer is a Cr metal layer or a Ti metal layer.
3. The wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing according to claim 1, characterized in that: The surface C layer is a graphite layer or a ta-C layer.
4. A method for preparing the wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step S1, glow cleaning; Step S2, high energy ion cleaning; Step S3, preparing a bonding layer; Step S4, preparing a wear-resistant self-lubricating coating; Step S5, preparing a surface C layer.
5. The method for preparing a wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing according to claim 4, characterized in that: The glow cleaning process is as follows: Set the argon flow rate to 80-150 sccm, the working gas pressure to 0.8-3.0 Pa, the bias power supply to -500-800 V, and the glow clearing time to 60-120 min.
6. The method for preparing a wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing according to claim 4, characterized in that: The high energy ion cleaning process is as follows: The argon gas flow rate is set to 80-100 sccm, the working gas pressure is set to 0.8-1.0 Pa, the high-power pulsed magnetron sputtering power supply target voltage pulse width is set to 1-4 μs, the average power is set to 5-8 kW and the negative bias power supply is set to -300-500 V, the sputtering target is Cr or Ti metal target, and the high-energy ion cleaning time is set to 5-10 minutes.
7. The method for preparing a wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing according to claim 4, characterized in that: The preparation process of the bonding layer is as follows: The argon flow rate is set to 80-100 sccm, the working gas pressure is set to 0.8-1.0 Pa, the high-power pulsed magnetron sputtering power supply target voltage pulse width is set to 1-4 μs, the average power is set to 5-8 kW and the negative bias power supply is set to -30--100 V, the sputtering target is Cr or Ti metal target, and the deposition time is set to 10-20 min.
8. The method for preparing a wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing according to claim 4, characterized in that: The preparation process of the wear-resistant self-lubricating coating is as follows: Set the argon flow rate to 80-100 sccm, the nitrogen flow rate to 20-60 sccm, the working gas pressure to 0.8-1.0 Pa, set the high-power pulsed magnetron sputtering power supply target voltage pulse width to 1-4 μs, the average power to 5-8 kW and the negative bias power supply to -30--100 V, the sputtering target materials are C target material and metal target material, or C target material and metal alloy target material, and the deposition time is 10-30 min.
9. The method for preparing a wear-resistant self-lubricating hydrogen-free carbon-based coating on the surface of an oil-free bearing according to claim 4, characterized in that: The surface C layer preparation process is as follows: Step S51, setting the oxygen flow rate to 80-150 sccm, the working pressure to 0.8-3.0 Pa, the bias power supply to -500-800 V, and the glow cleaning time to 5-10 min; Step S52, set the argon gas flow rate to 50-180sccm, the working gas pressure to 0.2-3Pa, set the high-power pulsed magnetron sputtering power supply target voltage pulse width to 10-50μs, the average power to 6-12kW and the bias power supply to -300--800V, the sputtering target material to C target material, and the deposition time to 5-20min.
Citation Information
Patent Citations
Amorphous carbon coating and preparation method and application thereof
CN101444985A
Surface anti-impact abrasion-resisting lubricating composite coating for hydraulic valve rod and preparation method thereof
CN109023362A
Hydrogen-free carbon film polymer lubricating material and preparation method and application thereof
CN113564527A
Ceramic dielectric filter surface coating method based on micro-arc ion plating and ceramic dielectric filter
CN114481014A
Hard carbon coatings with improved adhesion strength by means of hipims and method thereof
US20240093344A1
Cited By
GCr15 bearing steel surface graphite-like reinforced coating and preparation method thereof
CN121109975A